(untitled) (Nativa, 2024)
ABSTRACT: In the face of the rapid advancement of energy systems and the requirements of modern society, analyzing the impact of alternative energy sources on the sustainability of these systems is a significant issue for countries, with Ukraine being no exception. This paper meticulously examines alternative energy sources’ technical and engineering aspects, weighing their advantages and limitations in sustainable development. The objective is to identify the most effective strategies to bolster sustainable energy development in Ukraine, taking into account economic, environmental, and social aspects. The research adopts a comprehensive analytical approach, utilizing a mix of qualitative and quantitative methods, to assess the implications of alternative energy sources on the sustainability of energy systems within the context of Ukraine’s sustainable development. It reviews policy documents and international agreements to gain insights into the regulatory and economic landscape. It also analyzes trends in energy production, consumption, and investment in alternative energy projects in Ukraine, comparing them with traditional energy sources. However, this sector’s sustainable development hinges on providing adequate government support and creating a favorable business environment. The research underscores that one of the primary responsibilities of the Ukrainian government is to protect investors in RES and create the conditions for their continued operations. Keywords: sustainable development; alternative energy sources; energy efficiency; economic growth. Impactos das energias renováveis na sustentabilidade energética da Ucrânia RESUMO: Dado o rápido desenvolvimento dos sistemas energéticos e as necessidades da sociedade moderna, a análise do impacto das fontes alternativas de energia na sustentabilidade destes sistemas é uma questão importante para os países, especialmente a Ucrânia. Este artigo fornece uma análise aprofundada dos aspectos técnicos e de engenharia, das fontes alternativas de energia, e, avalia suas vantagens e limitações no desenvolvimento sustentável. Nesse sentido, o objetivo é identificar as melhores estratégias para apoiar o desenvolvimento energético sustentável na Ucrânia, considerando aspectos econômicos, ambientais e sociais. Adota-se uma abordagem analítica abrangente para avaliar as implicações das fontes alternativas de energia na sustentabilidade dos sistemas energéticos no contexto do desenvolvimento sustentável da Ucrânia. Foram revisados documentos políticos e acordos internacionais para compreender o panorama regulamentar e econômico. Foram analisadas tendências na produção, consumo e investimento de energia em projetos de energia alternativa na Ucrânia e comparadas com as fontes de energia tradicionais. No entanto, o desenvolvimento sustentável deste setor requer apoio governamental adequado e um ambiente empresarial favorável. Destaca-se que uma das principais tarefas do governo ucraniano nesse sentor, é proteger os investidores em RES e criar as condições para as suas futuras atividades. Palavras-chave: desenvolvimento sustentável; fontes de energia alternativa; eficiência energética; crescimento econômico.